AKTIVITAS MIKROORGANISME TANAH PADA TANAH BEKAS KEBAKARAN HUTAN DI KABUPATEN SAMOSIR - Agree Hutami Sinaga; Deni Elfiati; Delvian Delvian (Program studi Kehutanan USU, 2015)
Forest fire affect chemical, physical and biological properties of the soils. In the biological properties of the soil, forest fire also affects number of microorganisms and activity of microorganisms. The purpose of this research is calculate the value of soil microorganism with various periods of forest fires. The measure of the activities of microorganism using jar and titrimetri methods.The result of this research showed that value of respiration in unburn soil is 11,99. Value of respiration from forest fire soil in 2010 is 6,43. Value of respiration from forest fire soil in 2011 is 10,28. Value of respiration from forest fire soil in 2012 is 16,28. Value of respiration from forest fire soil in 2013 is 11,14. Value of respiration from forest fire soil in 2014 is 8,14. Activity of microorganisms is almost the same between the occurrence of fire with soil unburn. Keywords: forest fire, soil microorganism, activity of microorganism